Not quite us: anti-Catholic thought in English Canada since 1900 - Anderson, Kevin P. (McGill-Queen's studies in the history of religion, 2019)
Corrupting democracy : French Canada, immigration, and Anti-Catholicism in the "Progressive Era," 1900-1929 -- Fascism and the "revenge of the cradle" : anti-Catholicism and the Great Depression -- Conscription and the "omnicompetent state" : the Second World War and Anti-Catholicism -- What it means to be (truly) Canadian : Cold War Anti-Catholicism and the transformation of Britishness in Canada, 1945-1965 -- Anti-Catholicism, 1970s-1990s : the strange survival of an old prejudice.